Corporate tax avoidance and the upper echelon effect: Evidence from segment disclosure choices - Remerta Basson; Pieter V.A. van der Spuy (South African Journal of Economic and Management Sciences)
Background: The determinants of corporate tax avoidance are still not adequately understood, which necessitates an investigation of the influence of the upper-echelon effect as a determinant of corporate tax avoidance.